Szacunek, dystans, inkluzja. Paleta interaktywnych ćwiczeń do lekcji etyki (grupa wiekowa 10–14 lat) - Marsal, Eva; Dobashi, Takara; Nowak, Ewa (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
Authentic feelings like respect and similar moral emotions already start to develop in preverbal infants. However, our schooling systems offer only very few opportunities to train respectful behavior. Marsal, Dobashi, and Nowak introduce four interactive exercices in order to implement them in the moral and democratic education. All exercices are based on Martens’ Five Finger Method and on the didactic experiences made by authors in Germany, Japan, and Poland too.